Digital eye strain among university students: a cross-sectional study from Hyderabad, India - Bhammarkar, Umesh D. (International Journal of Research in Medical Sciences, 2025)
Background: Digital eye strain (DES) or computer vision syndrome (CVS) represents a growing public health concern as digital device usage increases globally, particularly among university students. This study aimed to assess the prevalence and characteristics of digital eye strain among university students in Hyderabad, India. Methods: A descriptive cross-sectional study was conducted among 112 university students in Hyderabad, India, from November to December 2024. Data was collected using a self-administered questionnaire. Non-probability convenience sampling was employed, and statistical analysis included calculation of percentages and means using statistical package for the social sciences (SPSS). Results: All participants (100%) owned smartphones, while 60.7% owned laptops. The mean age was 22.3±2.5 years, with 65.2% female participants. The most common symptoms reported were headache (75.0%), burning or itching sensation in eyes (50.0%), and watering from eyes (49.1%). Significant increases in screen time were observed over the preceding three years. Conclusions: Digital eye strain symptoms are highly prevalent among university students, with headaches being the predominant complaint. Preventive measures and awareness programs are essential to mitigate the effects of prolonged digital device usage on ocular health.